Naringenin: A potential anticancer drug - Yi Zhang; Haixin Ding; Xue Zhao; Yutong Li; Pengling Ge (Results in Chemistry)
Natural products, as vital bioactive components for human health maintenance, have garnered widespread attention for their medicinal value. Naringenin (NGE), a naturally occurring flavonoid abundant in citrus fruits, exhibits multiple pharmacological activities (including anti-inflammatory, antioxidant, neuroprotective, hepatoprotective, and anticancer effects), despite its pharmacokinetic limitations such as poor oral bioavailability and rapid metabolism. Research has demonstrated that NGE exhibits broad-spectrum anticancer activity by targeting multiple molecular mechanisms, including induction of tumor cell apoptosis, modulation of cell cycle progression, and interference with key signaling pathways such as TGF-β1, PI3K/AKT/mTOR, and NF-κB. Recent advances in nanodrug delivery systems have effectively addressed these pharmacokinetic limitations while substantially improving NGE's anticancer efficacy. This review systematically summarizes current research progress on NGE's natural sources, anticancer mechanisms, and novel delivery strategies, with the aim of providing a scientific foundation for NGE-based anticancer drug development and clinical translation.